Eccentric osteolytic lesion of the proximal tibia secondary to solitary bone plasmacytoma managed with reconstruction surgery: a case report - Kakkar, Rohil Singh; Kenjale, Randhir; Pareek, Ananya (International Surgery Journal, 2026)
Solitary bone plasmacytoma (SBP) is a rare plasma cell neoplasm characterized by localized monoclonal proliferation without systemic involvement, most commonly affecting the axial skeleton, while involvement of long bones such as the tibia remains distinctly uncommon. We report a case of a 51-year-old male presenting with progressive pain in the right proximal leg and difficulty in weight-bearing for three months. Clinical examination revealed localized tenderness over the medial proximal tibia with restricted knee motion. Radiographs demonstrated a well-defined eccentric osteolytic lesion with cortical breach and pathological fracture, while advanced imaging confirmed an intramedullary lesion with cortical destruction. Histopathological evaluation revealed sheets of malignant plasma cells, confirming plasmacytoma. Comprehensive systemic work-up, including skeletal survey, bone marrow biopsy, and biochemical analysis, excluded multiple myeloma. The patient underwent intralesional curettage followed by polymethylmethacrylate cement augmentation and proximal tibial locking plate fixation to restore structural stability. SBP involving the tibia is uncommon and may mimic other osteolytic lesions, necessitating thorough diagnostic evaluation to exclude systemic disease. Surgical management becomes essential in cases with structural compromise, where cement augmentation provides immediate mechanical stability, facilitates early mobilization, and may contribute to local tumor control. Intralesional curettage combined with cement-augmented internal fixation represents an effective reconstructive strategy for tibial SBP, enabling early weight-bearing and favorable functional outcomes. Long-term surveillance remains essential to monitor for progression to multiple myeloma.